Nursing Care for Stroke Patients: Strategies towards Patient-Centered Care - Seesawang, Junjira; Rungnoei, Nongnaphat (Nursing Science Journal of Thailand, 2016)
Abstract Stroke is an important neurological disease which is the leading cause of disability. In additions, stroke can affect patients both physical and psychological health resulted in necessity for long term care. This article aims to review literature related to current situations and consequences of stroke, as well as nursing strategies to enhance patient-centered care. Nurses can apply this knowledge in planning to care for stroke survivors to promote both physical and psychosocial recovery, prevent recurrence, and complications, in order to increase their quality of life. การพยาบาลผู้ป่วยโรคหลอดเลือดสมอง: กลยุทธ์สู่การดูแลแบบผู้ป่วยเป็นศูนย์กลาง บทคัดย่อ โรคหลอดเลือดสมองเป็นโรคที่สำคัญทางระบบประสาทที่เป็นสาเหตุนำไปสู่ความพิการนอกจากนี้โรคหลอดเลือดสมองยังส่งผลกระทบต่อร่างกายและจิตใจของผู้ป่วย รวมทั้ง ครอบครัวที่ดีต้องรับภาระในการดูแลระยะยาว บทความนี้มีวัตถุประสงค์เพื่อทบทวนวรรณกรรมที่เกี่ยวข้องกับสถานการณ์ปัจจุบันและผลกระทบของโรคหลอดเลือดสมอง รวมทั้งกลยุทธ์การดูแลแบบผู้ป่วยเป็นศูนย์กลาง ซึ่งพยาบาลสามารถนำความรู้ไปใช้ในการวางแผนการดูแลผู้ป่วยโรคหลอดเลือดสมอง เพื่อส่งเสริมการฟื้นฟูสภาพทั้งทางด้านร่างกายและจิตสังคม ป้องกันการกลับเป็นซํ้าและภาวะแทรกซ้อนต่างๆ และเพื่อส่งเสริมคุณภาพชีวิตของผู้ป่วย คำสำคัญ: โรคหลอดเลือดสมอง กลยุทธ์ การดูแลแบบผู้ป่วยเป็นศูนย์กลาง